Hubungan Tingkat Pengetahuan dan Sikap terhadap Kebiasaan Konsumsi Jamu pada Mayarakat Magelang Tahun 2019 - Tiara Mega Kusuma; Endaryanti Wulandari; Taufik Widiyanto; Diah Kartika (Universitas Muhammadiyah Surakarta)
Jamu is a cultural heritage of Indonesia that needs to be preserved. Jamu is classified as traditional medicine which is widely used by the community as an alternative treatment, especially Magelang city’s. This study aims to show relationship between the level of knowledge and attitudes towards the consumption habits of jamu in the community of Magelang. This research is included in a quantitative descriptive study with cross sectional approach with random sampling techniques. Data were obtained by surveying through the distribution of questionnaires and analyzed using the chi-square test (X2) to see each effect of the level of knowledge or attitudes towards herbal consumption habits based on p-value, and logistic regression tests to see the OR (Odds Ratio). The level of knowledge and attitudes about herbal medicine has a significant influence on the consumption habits of herbs with p-values of 0.003 and 0,000 (0.005). Attitude is proven to have the highest chance to improve the consumption habits of routine herbal medicine (23,262x) compared to the level of knowledge (1,273x).